CONDUCTIVE ADHESIVE COMPOSITION, ORGANIC ELECTRONICS DEVICE, AND METHOD FOR MANUFACTURING ORGANIC ELECTRONICS DEVICE - Patent application
The conductive adhesive composition with thermosetting resin, flux activator, and low-melting-point conductive particles addresses warping and reliability issues in organic electronic devices by enabling low-temperature mounting with effective electrical connections.
Patent Information
- Application Number
- JP2021035610
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-03-05
AI Technical Summary
Warping occurs in organic electronic devices during the heating process for mounting electronic components on a circuit board, and conventional anisotropic conductive adhesives struggle to ensure reliable electrical connections at low heating temperatures.
A conductive adhesive composition comprising a binder resin with a thermosetting resin and a flux activator, along with conductive particles made of metal with a melting point of 136° C. or less, is used to electrically connect the circuit board to electronic components, forming a reliable conductive path while minimizing warping.
The solution allows for the reliable mounting of electronic components on organic electronic devices with minimal warping, achieved through a low-temperature process that reduces thermal damage to organic elements.
Smart Images

Figure 0007647178000005 
Figure 0007647178000006 
Figure 0007647178000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to conductive adhesive compositions, organic electronic devices, and methods of making organic electronic devices. [Background technology]
[0002] An organic electronic device is generally a device having organic elements such as organic EL elements formed on a circuit board. In addition to the organic elements, other electronic components such as a driver IC are often mounted on the circuit board of the organic electronic device. In order to mount the electronic components on the circuit board of the organic electronic device while ensuring electrical connection, anisotropic conductive adhesives (ACFs) have been used in the past (e.g., Patent Document 1). The anisotropic conductive adhesive contains conductive particles, and the circuit board and the electronic components are electrically connected via a conductive path formed by contact between the conductive particles. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-140344 A Summary of the Invention [Problem to be solved by the invention]
[0004] Heating for mounting electronic components on a circuit board can cause warping in organic electronic devices. Although lower heating temperatures tend to reduce warping, it can be difficult to ensure sufficiently reliable electrical connections with conventional anisotropic conductive adhesives.
[0005] The present disclosure relates to a conductive adhesive composition that enables electronic components to be mounted on a circuit board of an organic electronic device with high reliability while suppressing warping. [Means for solving the problem]
[0006] One aspect of the present disclosure relates to a conductive adhesive composition containing a binder resin including a thermosetting resin and a flux activator, and conductive particles dispersed in the binder resin, and used to electrically connect a circuit board of an organic electronic device and an electronic component mounted on the circuit board. The conductive particles are metal particles including a metal part having a melting point of 136°C or less. The conductive particles have an average particle size of 1.0 to 30 μm. The flux activator contains a compound having a hydroxyl group and a carboxyl group.
[0007] Another aspect of the present disclosure relates to an organic electronics device comprising a substrate and a circuit board having two or more connection terminals provided on a main surface of the substrate, an organic element provided on the main surface of the substrate, an electronic component having two or more connection terminals facing the two or more connection terminals of the circuit board, and a connection portion disposed between the circuit board and the electronic component and joining them. The connection portion is a layer formed from the conductive adhesive composition. The connection portion includes a conductive portion interposed between the connection terminal of the circuit board and the connection terminal of the electronic component and electrically connecting them, and a resin portion formed around the conductive portion. The conductive portion is a metal layer formed by melting the conductive particles. The resin portion is a cured product formed from the binder resin. Effect of the Invention
[0008] According to one aspect of the present disclosure, electronic components can be mounted on a circuit board of an organic electronic device with high reliability while suppressing warping. In addition, since the electronic components can be mounted by a low-temperature process, thermal damage to the organic element can be suppressed. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a perspective view showing an example of an organic electronic device. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II in FIG. [Diagram 3] 1A to 1C are cross-sectional views illustrating an example of a method for manufacturing an organic electronic device. [Figure 4] 1A to 1C are cross-sectional views illustrating an example of a method for manufacturing an organic electronic device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, several embodiments of the present invention will be described in detail, however, the present invention is not limited to the following embodiments.
[0011] Fig. 1 is a perspective view showing an example of an organic electronic device. Fig. 2 is a cross-sectional view taken along line II-II in Fig. 1. The organic electronic device 100 shown in Figs. 1 and 2 is an organic EL panel having a circuit board 1, an organic EL element 2 (organic element) formed on the circuit board 1, and a driver IC 3 (electronic component) mounted on the circuit board 1.
[0012] The organic EL element 2 is composed of a cathode layer 21, an organic layer 25, and an anode layer 22, which are laminated in this order from the circuit board 1 side.
[0013] The cathode layer 21 may be a transparent conductive layer formed of a transparent conductive material such as ITO (indium tin oxide), AZO (aluminum zinc oxide), or IZO (indium zinc oxide). The organic layer 25 may be a laminated body composed of a hole injection layer, a hole transport layer, an organic light emitting layer, and an electron transport layer. The anode layer 22 may be a metal layer formed of a metal material including a metal element selected from Au, Ni, Al, Ag, Cu, Mg, Co, Li, and Zn, or an alloy containing these metal elements.
[0014] The organic electronic device 100 further includes a sealing substrate 6 that covers the organic EL element 2, and a sealant 7 provided between the peripheral portion of the sealing substrate 6 and the circuit board 1. An airtight space is formed on the circuit board 1 by the sealing substrate 6 and the sealant 7, and the organic EL element 2 is disposed in the airtight space.
[0015] The circuit board 1 has a base material 10 and a wiring section 4 formed on the main surface of the base material 10. The wiring section 4 includes a cathode wiring section 4a that connects the driver IC 3 and the cathode layer 21 of the organic EL element 2, an anode wiring section 4b that connects the driver IC 3 and the anode layer 22 of the organic EL element 2, and a connection wiring section 4c for inputting a power supply and various control signals to the driver IC 3. A flexible wiring board or the like is connected to the connection wiring section 4c. The wiring section 4 forms a connection terminal in the portion where the driver IC 3 is mounted.
[0016] The substrate 10 may be a transparent plate material, for example a glass plate, or may be a flexible substrate (for example a transparent resin film).
[0017] The driver IC 3 has an IC body 30 having a rectangular main surface, and two or more bumps 31 as connection terminals provided on the main surface of the IC body 30. The bumps 31 of the driver IC 3 are electrically connected to a wiring portion 4 as a connection terminal via a connection portion 5 formed from a conductive adhesive composition. The conductive adhesive composition will be described in detail later. Of the wiring portion 4, the portions that function as connection terminals connected to the driver IC 3 are provided at the same number and pitch as the bumps 31. The connection terminals of the circuit board (wiring portion 4) and the connection terminals of the driver IC 3 (bumps 31) are aligned so as to face each other.
[0018] In order to reduce the size and height of electronic components, it is required that the width of the bumps is narrow and that the intervals between the bumps are narrow. For example, the wiring portions 4 as connection terminals of the circuit board 1 may be arranged on the main surface of the base material 10 at intervals of 200 μm or less, or 100 μm or less. The intervals between the wiring portions 4 as connection terminals may be 10 μm or more.
[0019] 3 and 4 are cross-sectional views showing an example of a method for producing an organic electronic device, including a step of mounting a driver IC 3 (electronic component) on a circuit board 1. The method shown in Fig. 3 and 4 includes arranging the circuit board 1 and the driver IC 3 (electronic component) so that the wiring portion 4 (connection terminal) faces the bump 31 (connection terminal), and disposing a conductive adhesive composition 5A between the circuit board 1 and the driver IC 3, and heating and pressing a laminate composed of the circuit board 1, the conductive adhesive composition 5A, and the driver IC 3 with a thermocompression head 80, thereby forming a connection portion 5 from the conductive adhesive composition 5A.
[0020] The conductive adhesive composition 5A in a paste or liquid form may be applied onto the circuit board 1. Thereafter, the circuit board 1 may be placed on a stage of a connection device, and the circuit board 1, the conductive adhesive composition 5A, and the driver IC 3 may be heated and pressed by a thermocompression head 80 on the stage.
[0021] The conductive adhesive composition 5A includes a thermosetting binder resin 50A and a plurality of conductive particles 51A dispersed in the binder resin 50A. The thermocompression head 80 is heated to a predetermined connection temperature at which the conductive particles 51A melt. This connection temperature may be 130° C. or lower. While being heated to a predetermined connection temperature and pressurized by the thermocompression head 80, the binder resin 50A flows and flows out from between the bumps 31 of the driver IC 3 and the wiring portion 4 of the circuit board 1. At the same time, the molten conductive particles 51A fuse with each other to form a conductive portion 51 that is metal-bonded to the bumps 31 of the driver IC 3 and the wiring portion 4 of the circuit board 1. As a result, the bumps 31 and the wiring portion 4 are electrically connected via the conductive portion 51 interposed therebetween. The binder resin 50A hardens to form a resin portion 50, which is a hardened product, around the conductive portion 51. In other words, the conductive adhesive composition 5A melts and polarizes into the conductive portion 51 and the resin portion 50.
[0022] The conductive particles 51A in the conductive adhesive composition 5A may be particles containing a metal part having a melting point of 136°C or less. The conductive particles 51A may be metal particles composed only of particulate metal parts, or may be composite particles having a core particle made of a solid material other than metal and a layer-like metal part covering the surface of the core particle, or may be a combination of these. The solid material constituting the core particle may be, for example, ceramics, silica, a resin material, or a combination of these.
[0023] A metal part having a melting point of 136°C or less can form a conductive part 51 that melts at a low temperature that can suppress warping and enables electrical connection with good reliability. From a similar viewpoint, the melting point of the metal part may be 120°C or less. The lower limit of the melting point of the metal part is not particularly limited, but is, for example, about 60°C. When the metal part is an alloy containing two or more types of metals, it is sufficient that the melting point of the alloy is 136°C or less.
[0024] The metal portion usually contains one or more metals having a melting point of 136°C or less. The metal having a melting point of 136°C or less may be, for example, indium (In). The content of indium in the conductive particles 51A may be 10 to 70 mass% based on the mass of the conductive particles 51A. In order to obtain better connection reliability, the metal portion may further contain a metal having a high melting point within a range in which the melting point of the metal portion as a whole is 136°C or less. Examples of the metal having a high melting point include tin (Sn), zinc (Zn), platinum (Pt), gold (Au), silver (Ag), copper (Cu), nickel (Ni), palladium (Pd), and aluminum (Al).
[0025] The metal part of the conductive particle 51A may be an alloy containing indium and one or more high melting point metals selected from bismuth, tin, and zinc. For example, the conductive particle 51A may contain a metal part made of Sn50-In50 solder (melting point 120°C), Sn48-In52 solder (melting point 117°C), Bi67-In33 solder (melting point 109°C), Bi57-Sn17-In26 (melting point 79°C), Bi55-Sn25-In20 (melting point 79°C), Bi33.7-In66.3 (melting point 72°C), Bi32.5-Sn16.5-In51 (melting point 61°C), or a combination thereof. These alloys show clear solidification behavior after melting. The solidification behavior means that the metal cools and solidifies after melting. The conductive particles 51A may be metal particles made of a metal portion containing Sn50-In50 solder. Sn50-In50 refers to an alloy containing Sn and In in a mass ratio of Sn:In=50:50. The same applies to other alloys.
[0026] The conductive particles 51A may have an average particle size of 1.0 to 30 μm. If the conductive particles 51A have an average particle size of less than 1.0 μm, the viscosity of the conductive adhesive composition is high, so that workability tends to decrease, and the conductive particles are difficult to melt, so that good metal bonding tends to be difficult to form. If the conductive particles have an average particle size of more than 30 μm, short circuits may easily occur between connection terminals arranged at narrow intervals. From the same viewpoint, the conductive particles may have an average particle size of 2 to 25 μm. From the viewpoint of further improving the storage stability and connection reliability of the conductive adhesive composition, the conductive particles may have an average particle size of 5 to 20 μm. Here, the average particle size of the conductive particles is a value determined by a laser diffraction / scattering method.
[0027] The specific surface area of the conductive particles 51A is 0.001 to 3.0 m 2 When the specific surface area of the conductive particles 51A is within this range, the melting property of the solder particles during thermal connection is improved, and the insulation property between adjacent electrodes is improved.
[0028] The content of the conductive particles 51A may be 5 to 95% by mass relative to the mass of the conductive adhesive composition 5A. If the content of the conductive particles 51A is less than 5% by mass, the conductivity of the connection 5 formed from the conductive adhesive composition 5A tends to decrease. If the content of the conductive particles 51A is more than 95% by mass, the viscosity of the conductive adhesive composition increases, so that the workability tends to decrease, and the effect of improving the connection reliability tends to decrease relatively. From the same viewpoint, the content of the conductive particles 51A may be 10% by mass or more, 15% by mass or more, 50% by mass or more, or 60% by mass or more, and may be 90% by mass or less, or 85% by mass or less, relative to the mass of the conductive adhesive composition 5A.
[0029] The conductive adhesive composition 5A may further include high-melting conductive particles including a metal part having a melting point of more than 136°C in addition to the conductive particles 51A including a metal part having a melting point of 136°C or less. The metal having a melting point higher than 136°C may be, for example, one metal element selected from Sn, Bi, Pt, Au, Ag, Cu, Ni, Pd, and Al, or an alloy of two or more metals. Specific examples of high-melting conductive particles include Au powder, Ag powder, Cu powder, and Ag-plated Cu powder. As a commercially available product of high-melting conductive particles, "MA05K" (trade name, manufactured by Hitachi Chemical Co., Ltd.), which is a silver-plated copper powder, is available. Based on the total amount of the conductive particles including a metal part having a melting point of 136°C or less and the high-melting conductive particles, the proportion of the high-melting conductive particles may be 1 to 50 mass% or 1 to 40 mass%.
[0030] The binder resin 50A contains a thermosetting resin and a flux activator.
[0031] Thermosetting resins are organic compounds having reactive functional groups for curing, and examples thereof include epoxy resins, compounds having polymerizable carbon-carbon double bonds (e.g., (meth)acrylic resins, maleimide resins), and cyanate resins, as well as precursors thereof. (Meth)acrylic resins refer to methacrylic resins and acrylic resins. Thermosetting resins may contain compounds having polymerizable carbon-carbon double bonds, epoxy resins, or combinations thereof. These thermosetting resins have excellent heat resistance and adhesive properties, and can also be handled in a liquid state by dissolving or dispersing them in an organic solvent as necessary. From the viewpoints of availability and reliability, thermosetting resins may contain epoxy resins.
[0032] An epoxy resin is a compound having two or more epoxy groups, and examples thereof include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, epoxy resins having a naphthalene skeleton, aliphatic epoxy resins, glycidylamine type epoxy resins, and resorcin type epoxy resins.
[0033] Specific examples of commercially available epoxy resins include bisphenol A type epoxy resins AER-X8501 (manufactured by Asahi Kasei Corporation, product name), R-301 (manufactured by Mitsubishi Chemical Corporation, product name), and YL-980 (manufactured by Mitsubishi Chemical Corporation, product name), bisphenol F type epoxy resins YDF-170 (manufactured by Tohto Kasei Co., Ltd., product name), and YL-983U (manufactured by Mitsubishi Chemical Corporation, product name), bisphenol AD type epoxy resins R-1710 (manufactured by Mitsui Petrochemical Industries, Ltd., product name), and phenol N-730S (Dainippon Ink & Chemicals, Inc., product name), which is a cresol novolac type epoxy resin, Quatrex-2010 (Dow Chemical Co., Ltd., product name), YDCN-702S (Tohto Kasei Co., Ltd., product name), EOCN-100 (Nippon Kayaku Co., Ltd., product name), which is a cresol novolac type epoxy resin, EPPN-501 (Nippon Kayaku Co., Ltd., product name), TACTIX-742 (Dow Chemical Co., Ltd., product name), VG-3010 (Mitsui Petrochemical Co., Ltd., product name), which is a multifunctional epoxy resin, (manufactured by Mitsubishi Chemical Corporation, product name), 1032S (manufactured by Mitsubishi Chemical Corporation, product name), HP-4032 (manufactured by Dainippon Ink and Chemicals, Inc., product name), which is an epoxy resin having a naphthalene skeleton, EHPE-3150 and CEL-3000 (both manufactured by Daicel Chemical Industries, Ltd., product names), which are alicyclic epoxy resins, DME-100 (manufactured by New Japan Chemical Co., Ltd., product name), EX-216L (manufactured by Nagase Chemical Industries, Ltd., product name), W-100 (manufactured by New Japan Chemical Co., Ltd., product name), which is an aliphatic epoxy resin, and amine type Epoxy resins ELM-100 (manufactured by Sumitomo Chemical Co., Ltd., product name), YH-434L (manufactured by Tohto Kasei Co., Ltd., product name), TETRAD-X, TETRAD-C (both manufactured by Mitsubishi Gas Chemical Co., Ltd., product names), 630, 630LSD (both manufactured by Mitsubishi Chemical Co., Ltd., product names), resorcinol type epoxy resin Denacol EX-201 (manufactured by Nagase Chemical Industries, Ltd., product name), neopentyl glycol type epoxy resin Denacol EX-211 (manufactured by Nagase Chemical Industries, Ltd., product name), 1,Examples of such epoxy resins include Denacol EX-212 (trade name, manufactured by Nagase Chemical Industries, Ltd.), which is 6-hexanediol diglycidyl ether; Denacol EX series (EX-810, 811, 850, 851, 821, 830, 832, 841, 861 (all trade names, manufactured by Nagase Chemical Industries, Ltd.)), which is an ethylene-propylene glycol type epoxy resin; and E-XL-24 and E-XL-3L epoxy resins represented by the following general formula (I), which are both trade names manufactured by Mitsui Chemicals, Inc.
[0034] [ka] In formula (I), k represents an integer of 1 to 5.
[0035] The epoxy resins exemplified above may be used alone or in combination of two or more.
[0036] When the thermosetting resin contains an epoxy resin, the conductive adhesive composition 5A (or the binder resin 50A) may further contain a monofunctional epoxy compound having one epoxy group as a reactive diluent. Specific examples of commercially available monofunctional epoxy compounds include PGE (manufactured by Nippon Kayaku Co., Ltd., product name), PP-101 (manufactured by Tohto Kasei Co., Ltd., product name), ED-502, ED-509, ED-509S (manufactured by Asahi Denka Kogyo Co., Ltd., product name), YED-122 (manufactured by Yuka Shell Epoxy Co., Ltd., product name), KBM-403 (manufactured by Shin-Etsu Chemical Co., Ltd., product name), TSL-8350, TSL-8355, and TSL-9905 (manufactured by Toshiba Silicone Co., Ltd., product name). These may be used alone or in combination of two or more.
[0037] The content of the reactive diluent in the conductive adhesive composition 5A may be, for example, 0.1 to 30 mass % relative to the mass of the epoxy resin.
[0038] When the thermosetting resin contains an epoxy resin, the conductive adhesive composition 5A (or the binder resin 50A) may further contain a curing catalyst that promotes the curing reaction of the epoxy resin. The curing catalyst may be a compound having an imidazole group from the viewpoints of curability at a desired curing temperature, the length of pot life, the heat resistance of the cured product, and the like. Commercially available compounds having an imidazole group that can be used as a curing catalyst include 2P4MHZ-PW (2-phenyl-4-methyl-5-hydroxymethylimidazole), 2PHZ-PW (2-phenyl-4,5-dihydroxymethylimidazole), C11Z-CN (1-cyanoethyl-2-undecylimidazole), 2E4MZ-CN (1-cyanoethyl-2-ethyl-4-methylimidazole), 2PZ-CN (1-cyanoethyl-2-phenyl imidazole), 2MZ-A (2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine), 2E4MZ-A (2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine), 2MAOK-PW (2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct) (all of which are trade names manufactured by Shikoku Chemical Industry Co., Ltd.). These curing catalysts may be used alone or in combination of two or more.
[0039] The content of the curing catalyst may be 0.01 to 90 parts by mass, or 0.1 to 50 parts by mass, relative to 100 parts by mass of the epoxy resin. If the content of the curing catalyst is less than 0.01 parts by mass, the curability tends to decrease. If the content of the curing catalyst is more than 90 parts by mass, the handleability of the conductive adhesive composition 5A tends to decrease.
[0040] When the thermosetting resin contains an epoxy resin, the conductive adhesive composition 5A (or the binder resin 50A) may further contain a curing agent for adjusting the curing speed of the epoxy resin.
[0041] Examples of commercially available curing agents include phenol novolac resins H-1 (product name, manufactured by Meiwa Chemical Industry Co., Ltd.), VR-9300 (product name, manufactured by Mitsui Toatsu Chemicals Co., Ltd.), phenol aralkyl resin XL-225 (product name, manufactured by Mitsui Toatsu Chemicals Co., Ltd.), p-cresol novolac resin MTPC (product name, manufactured by Honshu Chemical Industry Co., Ltd.), allylated phenol novolac resin AL-VR-9300 (product name, manufactured by Mitsui Toatsu Chemicals Co., Ltd.), and special phenol resin PP-700-300 (product name, manufactured by Nippon Petrochemical Co., Ltd.).
[0042] The (meth)acrylic resin is a compound having a reactive functional group selected from an acryloyl group and a methacryloyl group, and examples thereof include a monoacrylate compound, a monomethacrylate compound, a diacrylate compound, and a dimethacrylate compound.
[0043] Examples of monoacrylate compounds include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, isodecyl acrylate, lauryl acrylate, tridecyl acrylate, hexadecyl acrylate, stearyl acrylate, isostearyl acrylate, cyclohexyl acrylate, isobornyl acrylate, diethylene glycol acrylate, polyethylene glycol acrylate, polypropylene glycol acrylate, 2-methoxyethyl acrylate, 2-methyl-2-phenylpropanediol ... ethyl acrylate, 2-ethoxyethyl acrylate, 2-butoxyethyl acrylate, methoxydiethylene glycol acrylate, methoxypolyethylene glycol acrylate, dicyclopentenyloxyethyl acrylate, 2-phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 2-benzoyloxyethyl acrylate, 2-hydroxy-3-phenoxypropyl acrylate, benzyl acrylate, 2-cyanoethyl acrylate, γ-acryloxyethyltrimethoxysilane, glycidyl acrylate, tetrahydrofurfuryl acrylate, dimethylaminoethyl acrylate, diethylaminoethyl acrylate, acryloxyethyl phosphate and acryloxyethylphenyl acid phosphate.
[0044] Examples of monomethacrylate compounds include methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, isodecyl methacrylate, lauryl methacrylate, tridecyl methacrylate, hexadecyl methacrylate, stearyl methacrylate, isostearyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, diethylene glycol methacrylate, polyethylene glycol methacrylate, polypropylene glycol methacrylate, 2-methoxyethyl methacrylate, methacrylate, 2-ethoxyethyl methacrylate, 2-butoxyethyl methacrylate, methoxydiethylene glycol methacrylate, methoxypolyethylene glycol methacrylate, dicyclopentenyloxyethyl methacrylate, 2-phenoxyethyl methacrylate, phenoxydiethylene glycol methacrylate, phenoxypolyethylene glycol methacrylate, 2-benzoyloxyethyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, benzyl methacrylate, 2-cyanoethyl methacrylate, γ-methacryloxyethyl trimethoxysilane, glycidyl methacrylate, tetrahydrofurfuryl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, methacryloxyethyl phosphate, and methacryloxyethyl phenyl acid phosphate.
[0045] Examples of diacrylate compounds include ethylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,3-butanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, tripropylene glycol diacrylate, polypropylene glycol diacrylate, a reaction product of 1 mole of bisphenol A, bisphenol F or bisphenol AD with 2 moles of glycidyl acrylate, diacrylates of polyethylene oxide adducts of bisphenol A, bisphenol F or bisphenol AD, diacrylates of polypropylene oxide adducts of bisphenol A, bisphenol F or bisphenol AD, bis(acryloxypropyl)polydimethylsiloxane and bis(acryloxypropyl)methylsiloxane-dimethylsiloxane copolymers.
[0046] Examples of dimethacrylate compounds include ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, tripropylene glycol dimethacrylate, polypropylene glycol dimethacrylate, a reaction product of 1 mole of bisphenol A, bisphenol F or bisphenol AD with 2 moles of glycidyl methacrylate, dimethacrylate of a polyethylene oxide adduct of bisphenol A, bisphenol F or bisphenol AD, a polypropylene oxide adduct of bisphenol F or bisphenol AD, bis(methacryloxypropyl)polydimethylsiloxane and bis(methacryloxypropyl)methylsiloxane-dimethylsiloxane copolymer.
[0047] The above-exemplified compounds may be used alone or in combination of two or more.
[0048] Specific examples of commercially available (meth)acrylic resins include FINEDIC A-261 (trade name, manufactured by Dainippon Ink and Chemicals, Inc.) and FINEDIC A-229-30 (trade name, manufactured by Dainippon Ink and Chemicals, Inc.).
[0049] When the thermosetting resin contains a (meth)acrylic resin, the conductive adhesive composition 5A (or the binder resin 50A) may contain a radical polymerization initiator. The radical polymerization initiator may be an organic peroxide or an azo compound, and may be an organic peroxide from the viewpoint of suppressing voids. From the viewpoint of improving the curability and viscosity stability of the binder resin 50A, the decomposition temperature of the organic peroxide may be 130°C to 200°C.
[0050] Examples of organic peroxides include benzoyl peroxide and t-butylperoxy-2-ethylhexanoate. Examples of azo compounds include azobisisobutyronitrile and azobisdimethylvaleronitrile.
[0051] The content of the radical polymerization initiator may be 0.01 to 20 mass %, 0.1 to 10 mass %, or 0.5 to 5 mass % relative to the mass of the conductive adhesive composition 5A.
[0052] The content of the thermosetting resin may be 1 to 60 mass %, 5 to 40 mass %, or 10 to 30 mass % relative to the mass of the conductive adhesive composition 5A.
[0053] The flux activator is a component that exhibits the function of removing an oxide film formed on the surface of the conductive particles. When the oxide film is removed by the flux activator, the conductive particles 51A melt and are likely to form the conductive part 51. The flux activator according to one embodiment includes a compound containing a hydroxyl group and a carboxyl group. The compound having a hydroxyl group and a carboxyl group may be an aliphatic dihydroxycarboxylic acid from the viewpoint of efficient removal of the oxide film. The aliphatic dihydroxycarboxylic acid may be a compound represented by the following general formula (V), tartaric acid, or a combination thereof.
[0054] [ka]
[0055] In formula (V), R5 represents an alkyl group having 1 to 5 carbon atoms and may be a methyl group, an ethyl group, or a propyl group. n and m each independently represent an integer of 0 to 5. n may be 0 and m may be 1, or both n and m may be 1.
[0056] Examples of the compound represented by the general formula (V) include 2,2-bis(hydroxymethyl)propionic acid, 2,2-bis(hydroxymethyl)butanoic acid, and 2,2-bis(hydroxymethyl)pentanoic acid, etc. The flux activator may contain at least one compound selected from these.
[0057] The content of the flux activator may be 0.5 to 50 mass%, 0.5 to 40 mass%, 1.0 to 35 mass%, or 4.0 to 8.5 mass% relative to the mass of the conductive particles. If the content of the flux activator is less than 0.5 mass%, the effect of improving connection reliability tends to be relatively small. If the content of the flux activator is more than 50 mass%, the storage stability and printability of the conductive adhesive composition 5A tend to decrease.
[0058] The conductive adhesive composition 5A may further contain additives in addition to the above-mentioned components, which may be one or more additives selected from the group consisting of a plasticizer for stress relaxation, a diluent for improving workability, an adhesive strength improver, a wettability improver, and an antifoaming agent.
[0059] Examples of the flexibilizing agent include liquid polybutadiene (manufactured by Ube Industries, Ltd. under the trade names "CTBN-1300x31" and "CTBN-1300x9" and manufactured by Nippon Soda Co., Ltd. under the trade name "NISSO-PB-C-2000"). The content of the flexibilizing agent may be 0.1 to 500 parts by mass with respect to 100 parts by mass of the thermosetting resin.
[0060] The conductive adhesive composition 5A may contain a coupling agent such as a silane coupling agent or a titanium coupling agent for the purpose of improving adhesive strength. An example of a commercially available silane coupling agent is "KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd. The conductive adhesive composition may contain a surfactant such as an anionic surfactant or a fluorine-based surfactant for the purpose of improving wettability. The conductive adhesive composition may contain silicone oil or the like as an antifoaming agent. The content of the coupling agent, the surfactant, and the antifoaming agent may be 0.1 to 10% by mass relative to the mass of the conductive adhesive composition 5A.
[0061] The conductive adhesive composition 5A may contain a diluent as necessary from the viewpoint of coating workability. The diluent may be, for example, an organic solvent selected from butyl carbitol, butyl carbitol acetate, butyl cellosolve, carbitol, butyl cellosolve acetate, carbitol acetate, dipropylene glycol monomethyl ether, ethylene glycol diethyl ether, and α-terpineol. The content of the diluent may be 0.1 to 30% by mass relative to the mass of the conductive adhesive composition 5A.
[0062] The conductive adhesive composition 5A may contain a non-conductive filler. Examples of the non-conductive filler include polymer particles such as acrylic rubber and polystyrene, and inorganic particles such as diamond, boron nitride, aluminum nitride, alumina, and silica. These fillers may be used alone or in combination of two or more.
[0063] The conductive adhesive composition 5A may be in a paste form at 25° C. The conductive adhesive composition 5A may have a viscosity at 25° C. of 5 to 400 Pa·s.
[0064] The conductive adhesive composition 5A can be obtained by mixing, dissolving, degranulating, kneading or dispersing each component at once or in a number of batches, while heating as necessary.
[0065] By applying the conductive adhesive composition according to the present disclosure, a driver IC 3 (electronic component) can be mounted on a circuit board 1 by heating and pressing (thermocompression bonding) at a low temperature. Compared with the case of using an anisotropic conductive material (ACF) that is generally used and requires thermocompression bonding at a higher temperature, thermal damage to the organic layer 25, which has particularly low heat resistance, is reduced. The low heating temperature for mounting electronic components also contributes to reducing warpage. The temperature (connection temperature) of thermocompression bonding for mounting electronic components with the formation of a connection part from the conductive adhesive composition may be 130°C or lower, or may be 100°C or higher. The pressure of thermocompression bonding may be 0.5 to 20 MPa. The time of thermocompression bonding may be 5.0 to 120 seconds.
[0066] The conductive adhesive composition according to the present disclosure is also advantageous in terms of connection reliability when the connection terminals are narrow and arranged at close intervals. In the case of an anisotropic conductive agent, when the connection terminals are narrow, the number of conductive particles in contact with the connection terminals tends to be insufficient, which leads to an increase in conduction resistance. As a result, for example, when a large current flows through an organic element, the wiring part may locally heat up and break. In the case of the conductive adhesive composition according to the present disclosure, the conductive particles are integrated to form a conductive part, and a conductive path is formed by metal bonding of the conductive part, so that even if the connection terminal is narrow, a sufficiently low conduction resistance is easily maintained.
[0067] Connections using the conductive adhesive composition according to the present disclosure do not require temporary compression bonding prior to thermocompression bonding, and are therefore advantageous in terms of process simplification compared to ACF, which often requires temporary compression bonding.
[0068] Although the embodiments of the present disclosure have been described above in detail, they can be modified as necessary. For example, the organic element is not limited to an organic EL element, and may be an element including an organic layer having various functions. Other examples of the organic element include an organic thin-film solar cell and an organic image sensor element. The electronic components mounted on the circuit board are not limited to a driver IC, and may be, for example, a sensor element, a module component having a sensor element, a Schottky barrier diode, or a thermoelectric conversion element. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0070] 1.Material (A) Conductive particles Sn50-In50 solder particles (18μm): Manufactured by 5NPLUS, melting point: 120℃, average particle size 18μm Sn50-In50 solder particles (5μm): Manufactured by 5NPLUS, melting point 120℃, average particle size 5μm Bi67-In33 solder particles (12μm): Manufactured by 5NPLUS, melting point 109℃, average particle size 12μm Bi57-Sn17-In26 solder particles (13μm): Manufactured by 5NPLUS, melting point 79℃, average particle size 13μm Bi33.7-In66.3 solder particles (13μm): Manufactured by 5NPLUS, melting point 72℃, average particle size 13μm Bi32.5-Sn16.5-In51 solder particles (14μm): Manufactured by 5NPLUS, melting point 61℃, average particle size 14μm Sn42-Bi58 solder particles (10~25μm): Manufactured by 5NPLUS, melting point 138℃, average particle size 10~25μm (B) Thermosetting resin YL980: Bisphenol F type epoxy resin manufactured by Mitsubishi Chemical Corporation (C) Flux activator ·BHPA: 2,2-bis(hydroxymethyl)propionic acid BHBA: 2,2-bis(hydroxymethyl)butanoic acid Glutaric acid Adipic Acid (D) Curing catalyst 2P4MHZ-PW: Shikoku Chemical Industry Co., Ltd., imidazole compound
[0071] 2.Conductive adhesive composition Example 1 22.5 parts by mass of YL980, 1.1 parts by mass of 2P4MHZ-PW, and 6.4 parts by mass of BHPA were mixed, and the mixture was passed through a triple roll three times to prepare a binder resin component. 70 parts by mass of Sn50-In50 solder particles (average particle size 18 μm) were added to 30 parts by mass of the binder resin component, and the resulting mixture was stirred using a planetary mixer. The mixture after stirring was degassed at 500 Pa or less for 10 minutes to obtain a paste-like conductive adhesive composition.
[0072] Examples 2 to 9, Comparative Examples 1 to 3 A conductive adhesive composition was obtained in the same manner as in Example 1, except that the types and compounding ratios of the materials were changed as shown in Table 1 or Table 2.
[0073] Comparative Examples 4 to 7 The following commercially available conductive adhesive compositions were prepared: Sn42-Bi58 cream solder: Eco Solder (product name), manufactured by Senju Metal Industry Co., Ltd. Sn96.5-Ag3-Cu0.5 solder paste: Eco Solder (product name), manufactured by Senju Metal Industry Co., Ltd. Anisotropic conductive film (ACF for COG): ANISOLM (product name) manufactured by Showa Denko Materials
[0074] 3. Preparation of the connector Example 1 An evaluation IC was prepared with dimensions of 1.5 mm x 15 mm, thickness of 0.45 mm, bump (Au-plated) area of 40 μ x 125 μm, and space between bumps of 15.0 μm. An evaluation circuit board was prepared with a glass substrate with dimensions of 25 mm x 040 mm and thickness of 0.25 mm and a wiring pattern formed on the glass substrate. The wiring pattern was formed from an ITO film plated with Ni-Au, and had a comb-shaped pattern of the same size and pitch as the bumps of the evaluation IC.
[0075] The conductive adhesive composition of Example 1 was applied to the circuit board for evaluation. The IC for evaluation was placed on the circuit board for evaluation so that the applied conductive adhesive composition was sandwiched between them. At that time, the bumps of the IC for evaluation were aligned with the electrode pattern of the circuit board for evaluation. Next, a laminate consisting of the circuit board for evaluation, the conductive adhesive composition, and the IC for evaluation was heated and pressed by a thermocompression head under conditions of 125°C, 10 MPa, and 30 seconds, thereby obtaining a connection for evaluation.
[0076] Examples 2 to 9, Comparative Examples 1 to 8 A connection body for evaluation was prepared in the same manner as in Example 1, except that the conductive adhesive composition and, in some cases, the connection temperature (temperature of the thermocompression head) were changed as shown in Tables 1 and 2. However, in the case of Comparative Example 6, the thermocompression bonding conditions were changed to 180°C, 80 MPa, and 5 seconds. The 160°C used in Comparative Example 4 is the standard connection temperature for SnBi solder paste. The 260°C used in Comparative Example 5 is the standard connection temperature for SnAgCu solder paste.
[0077] 4. Evaluation The connections of the examples and comparative examples were evaluated for the following items. The evaluation results are shown in Tables 1 and 2.
[0078] (1) Conduction resistance value The connectors were subjected to a reliability test in which temperature cycles between -40°C and 85°C were repeated for 10,000 hours. The electrical resistance of each connector was measured using a simple tester initially (before the reliability test) and after the reliability test. "OR" in the table indicates that the electrical conductivity was extremely low, resulting in a high electrical resistance value that exceeded the measurable range.
[0079] (2) Warpage The height (displacement) from a reference position on the surface opposite the electrode pattern of the evaluation wiring board before the evaluation IC was mounted was measured using a warpage measuring device (manufactured by AKROMETRIX, product name: THERMOIRE PS200). The difference between the maximum and minimum displacement was recorded as the initial shape value. The height (displacement) from a reference position on the surface opposite the evaluation IC of the fabricated connection body was measured. The difference between the maximum and minimum displacement was recorded as the post-mounting shape value. The value obtained by subtracting the initial shape value from the post-mounting shape value was taken as the amount of warpage.
[0080] [Table 1]
[0081] [Table 2]
[0082] All of Examples 1 to 9 exhibited good electrical conductivity, and almost no decrease in electrical conductivity was observed after the reliability test. A sufficiently low amount of warpage of 2 μm or less was also observed.
[0083] In the case of Comparative Example 1, in which conductive particles with a melting point of 138°C were used, the initial conductivity could not be secured, and the conductive resistance value was over-range (OR). This is thought to be because the Sn42-Bi58 solder particles did not melt under the connection temperature condition of 125°C.
[0084] The initial conduction resistance values of Comparative Examples 2 and 3, in which a flux activator having no hydroxyl group was used, were lower than the initial conduction resistance values of Examples 1 to 9. After the reliability test, the conduction resistance value further increased.
[0085] The conduction resistance values of Comparative Examples 4 and 5 were initially good, but increased to 10 times or more the initial value after the reliability test. The warpage amounts of Comparative Examples 4 and 5 were about twice or more the warpage amounts of Examples 1 to 9. This suggests that the difference in connection temperature causes the increase in the warpage amount.
[0086] The conduction resistance value of Comparative Example 6, in which the ACF for COG was used, was initially good, but increased to 15 times the initial value after the reliability test. The amount of warping of Comparative Example 6 was about four times that of Examples 1 to 9. It was confirmed that the amount of warping increased due to the high connection temperature.
[0087] In the case of Comparative Example 7, in which a COG ACF was used and a connection body was produced under the same connection conditions as those of Examples 1 to 9, the initial conduction resistance value increased, and an even higher conduction resistance value was observed after the reliability test. In the case of ACF, it was confirmed that when the connection temperature was low, the amount of warping decreased, but sufficient conduction was not ensured. [Explanation of symbols]
[0088] Reference Signs List 1...circuit board, 2...organic EL element (organic element), 3...driver IC (electronic component), 4...wiring portion (connection terminal), 4a...cathode wiring portion, 4b...anode wiring portion, 4c...connection wiring portion, 5...connection portion, 5A...conductive adhesive composition, 6...sealing substrate, 7...sealing material, 10...substrate, 21...cathode layer, 22...anode layer, 25...organic layer, 30...IC main body portion, 31...bump (connection terminal), 50...resin portion, 50A...conductive adhesive composition, 51...conductive portion, 51A...conductive particles.
Claims
1. a binder resin including a thermosetting resin and a flux activator; Conductive particles dispersed in the binder resin; Including, The conductive particles include a metal portion having a melting point of 136° C. or less, The conductive particles have an average particle size of 12 to 30 μm; the flux activator includes a compound having a hydroxyl group and a carboxyl group, A conductive adhesive composition used for electrically connecting a circuit board of an organic electronic device and an electronic component mounted on the circuit board.
2. The conductive adhesive composition according to claim 1, wherein the content of the flux activator is 4.0 to 8.5 mass % based on the mass of the conductive particles.
3. The conductive adhesive composition according to claim 1 or 2, wherein the metal portion contains indium.
4. The conductive adhesive composition according to claim 3, wherein the indium content in the metal portion is 10 to 70 mass % based on the mass of the metal portion.
5. The specific surface area of the conductive particles is 0.001 to 3.0 m 2 The conductive adhesive composition according to any one of claims 1 to 4, wherein the conductive adhesive composition has a viscosity of 1000 MPa (Apparent viscosity) ...
6. The conductive adhesive composition according to any one of claims 1 to 5, wherein the thermosetting resin comprises an epoxy resin.
7. The conductive adhesive composition according to claim 6 , further comprising a curing catalyst that accelerates the curing reaction of the epoxy resin.
8. The conductive adhesive composition according to any one of claims 1 to 7, wherein the conductive adhesive composition is in a paste form at 25°C.
9. the circuit board has a base material and two or more connection terminals provided on a main surface of the base material, The electronic component has two or more connection terminals, The conductive adhesive composition according to any one of claims 1 to 8, which is used to electrically connect the circuit board and the electronic component by forming a conductive portion interposed between a connection terminal of the circuit board and a connection terminal of the electronic component by melting the conductive particles.
10. The conductive adhesive composition according to claim 9 , wherein the two or more connection terminals of the circuit board are arranged on the main surface of the base material at intervals of 200 μm or less from each other.
11. a circuit board having a base material and two or more connection terminals provided on a main surface of the base material; an organic element provided on a main surface of the substrate; an electronic component having two or more connection terminals facing the two or more connection terminals of the circuit board; a connection portion disposed between the circuit board and the electronic component and joining them; Equipped with The connection portion is a layer formed from the conductive adhesive composition according to any one of claims 1 to 8, the connection portion includes a conductive portion interposed between the connection terminal of the circuit board and the connection terminal of the electronic component and electrically connecting them, and a resin portion formed around the conductive portion, the conductive portion being a metal layer formed by melting the conductive particles, and the resin portion being a cured product formed from the binder resin; Organic electronic devices.
12. 12. The organic electronic device according to claim 11, wherein the electronic component is at least one selected from the group consisting of a driver IC, a sensor element, a module component having a sensor element, a Schottky barrier diode, and a thermoelectric conversion element.
13. 13. The organic electronic device of claim 11 or 12, wherein the substrate is a flexible substrate.
14. A circuit board having a substrate and two or more connection terminals provided on a main surface of the substrate, and an electronic component having a connection terminal are arranged so that the connection terminals of the circuit board face the connection terminals of the electronic component, and the conductive adhesive composition according to any one of claims 1 to 8 is arranged between the circuit board and the electronic component; applying heat and pressure to a laminate composed of the circuit board, the conductive adhesive composition, and the electronic component, thereby forming a connection portion from the conductive adhesive composition that is disposed between the circuit board and the electronic component and joins them; in that order, the connection portion includes a conductive portion interposed between the connection terminal of the circuit board and the connection terminal of the electronic component and electrically connecting them, and a resin portion formed around the conductive portion, the conductive portion being a metal layer formed by melting the conductive particles, and the resin portion being a cured product formed from the binder resin; A method for manufacturing an organic electronic device.
Citation Information
Patent Citations
Heat or active energy ray-curable adhesive
JP2008214449A
COG type panel and organic el panel
JP2019140344A
Electroconductive adhesive composition and connection structure using same
WO2019013336A1